2020
DOI: 10.1016/j.seizure.2020.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Risks of seizure with fatal traffic crash at wheel in people with epilepsy

Abstract: The Japanese authorities require a 2-year seizure-free period for a driver's license in people with epilepsy. To evaluate the stringency of the criteria, we calculated the risk of fatal traffic crashes by epileptic seizure and compared that to the risk of fatal traffic crashes among the general population. Methods: Nation-wide questionnaire surveys to physicians and their patients with epilepsy were conducted to determine the rate of seizure recurrence after given seizure-free periods, average driving time and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It has been estimated that 64-73% of adult epilepsy patients drive some kind of vehicle (Classen et al, 2012); 26-28% reported that they had had a car accident, but only 11% of these accidents were seizure-related (Lossius et al, 2010). While 31-38% of seizures while driving would precipitate a traffic accident, according to a recent retrospective survey in Japan (Nishida et al, 2020), in only up to 5% was some type of physical injury determined. For PWE, traffic accident rates were estimated to be 1.13-2.16fold higher than that of the general population, but results are conflicting (Classen et al, 2012).…”
Section: Traffic Accidents As a Cause Of Seizure-related Injury Or Deathmentioning
confidence: 99%
“…It has been estimated that 64-73% of adult epilepsy patients drive some kind of vehicle (Classen et al, 2012); 26-28% reported that they had had a car accident, but only 11% of these accidents were seizure-related (Lossius et al, 2010). While 31-38% of seizures while driving would precipitate a traffic accident, according to a recent retrospective survey in Japan (Nishida et al, 2020), in only up to 5% was some type of physical injury determined. For PWE, traffic accident rates were estimated to be 1.13-2.16fold higher than that of the general population, but results are conflicting (Classen et al, 2012).…”
Section: Traffic Accidents As a Cause Of Seizure-related Injury Or Deathmentioning
confidence: 99%
“…7 This risk-based approach formed the basis for the current European directive 8 and has been used in several international publications on driving issues. [9][10][11][12][13] In the United Kingdom, the acceptable risk was adopted and set to a cutoff of 20% by the neurology panel of the Driver and Vehicle Licensing Agency (DVLA). 9 Systematic, longer-term data on ReR of patients with NMDAR-, LGI1-, CASPR2-, or GABA B R-AIE, who are seizure-free following resolution of the initial illness, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…7 This risk-based approach formed the basis for the current European directive 8 and has been used in several international publications on driving issues. 9-13 In the United Kingdom, the acceptable risk was adopted and set to a cutoff of 20% by the neurology panel of the Driver and Vehicle Licensing Agency (DVLA). 9…”
Section: Introductionmentioning
confidence: 99%